Jak to z kołem i obtaczaniem być mogło. Innowacje i techniki we wczesnośredniowiecznej ceramice – nieustannie aktualny problem - Kinga Zamelska-Monczak (Przegląd Archeologiczny)
The article engages with the issue of changes in the technology of producing clay vessels based on the example of early medieval pottery from Wielkopolska. The focus was on the issue of the introduction of innovations and the process of technological change from the perspective of the techniques used and their importance in a broader cultural and social context. Ecological, economic and technical factors are indicated as the main reasons for changes in the technological style, while less importance is attached to social behaviour or cultural norms. Pottery making is a social act, as it takes place in a specific community with its own tradition and past, specific preferences and cultural patterns. Pottery production techniques, more resistant to change than form or ornament, have become a good variable for identifying cultural groups and recognizing communication between communities and relationships between their members. The presented comments and interpretations indicate the research potential of the analysis of technology and innovations emerging in this process.